Electrochemical behavior of copper in drinking water: evaluation of dissolution process at low anodic overpotential (2011)
The electrochemical behavior of copper in near-neutral aerated tap water was studied by potentiodynamic polarization and electrochemical impedance spectroscopy up to four days of immersion under different hydrodynamic conditions. The impedance results were interpreted by equivalent circuit that showed an increasing film thickness with time that hinders the diffusion of copper species across the oxide layer, which is larger in stagnating condition. At low anodic overpotential, copper impedance presents at least four time constants that could be explained by faradaic processes, adsorption/desorption of intermediate species, diffusion controlled process and oxide layer formation on copper surface. In the anodic region, the overall corrosion resistance decreases possibly due to the dissolution of copper species and the increase of diffusion across the oxide layer, mainly under hydrodynamic condition.